Personal Higiene terhadap Kontaminasi Bakteri Salmonella sp pada Es Campur - Normalisa Ella Yunarti; Rahmawati Rahmawati; Erminawati Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
Mixed ice is a beverage that is very popular with people and is very easy to find. Traders mixed ice that their hygiene is not quite right; it is very easily contaminated by pathogen bacteria. Landasan Ulin District as a trading centre in Kota Banjarbaru makes it strategic place so many mixed ice traders found in this District. This study was aiming to determine the traders mixed ice's hygiene with the contamination of Salmonella sp bacteria in blended ice. This type of research was an analytical survey with a cross-sectional study design. Data were collected by observing, interviewing and examining samples, as many as 23 mixed ice samples were analysing of salmonella sp bacteria. Data analysis was performing using Somer's d correlation test. The results showed that there was a significant correlation between personal hygiene of mixed ice traders with Salmonella sp bacteria with a negative correlation direction which could be a conclusion that the higher the personal hygiene score of combined ice traders, the Salmonella sp bacteria would be harmful in mixed ice. It is suggested to the next researcher to check the Salmonella sp bacteria on each component of blended ice so that they will know at what stage Salmonella sp bacteria have contaminated the ice mixed.